Multi-country analysis of the effects of diarrhoea on childhood stunting - Checkley, William; Buckley, Gillian; Gilman, Robert H; Assis, Ana Mo; Guerrant, Richard L; Morris, Saul S; Mølbak, Kåre; Valentiner-Branth, Palle; Lanata, Claudio F; Black, Robert E (International journal of epidemiology, 2008)
Diarrhoea is an important cause of death and illness among children in developing countries; however, it remains controversial as to whether diarrhoea leads to stunting. We conducted a pooled analysis of nine studies that collected daily diarrhoea morbidity and longitudinal anthropometry to determine the effects of the longitudinal history of diarrhoea prior to 24 months on stunting at age 24 months. Data covered a 20-year period and five countries. We used logistic regression to model the effect of diarrhoea on stunting. The prevalence of stunting at age 24 months varied by study (range 21-90%), as did the longitudinal history of diarrhoea prior to 24 months (incidence range 3.6-13.4 episodes per child-year, prevalence range 2.4-16.3%). The effect of diarrhoea on stunting, however, was similar across studies. The odds of stunting at age 24 months increased multiplicatively with each diarrhoeal episode and with each day of diarrhoea before 24 months (all P < 0.001). The adjusted odds of stunting increased by 1.13 for every five episodes (95% CI 1.07-1.19), and by 1.16 for every 5% unit increase in longitudinal prevalence (95% CI 1.07-1.25). In this assembled sample of 24-month-old children, the proportion of stunting attributed to >or=5 diarrhoeal episodes before 24 months was 25% (95% CI 8-38%) and that attributed to being ill with diarrhoea for >or=2% of the time before 24 months was 18% (95% CI 1-31%). These observations are consistent with the hypothesis that a higher cumulative burden of diarrhoea increases the risk of stunting.